A Cross-Sectional Study Comparing the Prevalence of Bullous Pemphigoid Autoantibodies in 275 Cases of Type II Diabetes Mellitus Treated With or Without Dipeptidyl Peptidase-IV Inhibitors - Izumi, Kentaro (Front Immunol, 2019)
Background: Anti-hyperglycemic drug dipeptidyl peptidase-IV inhibitors (DPP-4i) have recently been recognized as bullous pemphigoid (BP) inducing drugs. It remains uncertain whether DPP-4i induce BP-IgG autoantibodies before the onset of BP. Objective: To evaluate the effect of DPP-4i in the development of BP-IgG autoantibodies in type 2 diabetes mellitus (T2DM) patients. Methods: A cross-sectional study on 221 DPP-4i (+) and 54 DPP-4i (–) T2DM cases was conducted. BP180 NC16A, BP230, and full-length BP180 ELISAs were used to detect the BP-IgG autoantibodies. We have also statistically analyzed the proportion of age, gender, intake periods of DPP-4i, and hemoglobin A1c level between anti-full-length BP180 IgG-positive and -negative DPP-4i (+) T2DM cases to identify co-founding factors. Results: BP180 NC16A ELISA, BP230 ELISA, and full-length BP180 ELISA were positive in 1.8, 2.2, and 10.9% of DPP-4i (+) T2DM cases, respectively; in contrast, they were positive in 0, 7.4, and 5.6% of DPP-4i (–) T2DM cases, respectively. The odds ratio for the development of BP-IgG autoantibodies detected by full-length BP180 ELISA was 2.070 for DPP-4i (+). There were no significant differences between the genders, intake periods of DPP-4i, nor of hemoglobin A1c levels, the anti-full-length BP180 IgG-positive cases tended to be significantly older than anti-full-length BP180 IgG-negative cases (median 74 vs. 69, p = 0.025) in the DPP-4i (+) T2DM cases. Limitations: We focused the analysis on DPP-4i intake and not on the effects of metformin and other drugs. Conclusion: Exposure to specific DPP-4i may induce the development of anti-full-length BP180 autoantibodies even in T2DM patients without any clinical symptoms of BP. Aging would be a risk factor to develop anti-full-length BP180-IgG autoantibody in DPP-4i (+) T2DM cases.